Analisis Pola Spasial Sebaran Dan Karakteristik Usaha Coffee Shop di Kelurahan Wai Mhorock - Yeremia Petra Vicky Merahabia; Irja Tobawan Simbiak; Sudiro Sudiro (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
This study aims to analyze the spatial distribution patterns and business characteristics of Coffee Shops in Wai Mhorock Sub-district, Abepura District, Jayapura City. The rapid growth of Coffee Shops in this area is influenced by its strategic location, situated near educational institutions, shopping centers, and social activity hubs. The research employs a quantitative approach with spatial mapping techniques using Geographic Information Systems (GIS) and field surveys to identify the characteristics of each business. The results show that the spatial distribution of Coffee Shops in Wai Mhorock tends to be clustered, with a high concentration along main roads and community activity centers. The characteristics of the businesses vary in terms of venue concept, types of menus offered, operational hours, supporting facilities, and target consumers. Most Coffee Shops target young people such as students and university attendees by offering a cozy atmosphere and free internet access. In conclusion, understanding the spatial patterns and business characteristics of Coffee Shops can serve as a foundation for sustainable urban spatial planning and business development. This study also provides recommendations for entrepreneurs and local governments to consider location, accessibility, and environmental impacts in managing commercial space.